Emerson in his own time : a biographical chronicle of his life, drawn from recollections, interviews, and memoirs by family, friends, and associates - Bosco, Ronald A.; Myerson, Joel (University of Iowa Press, 2003)
In sixteen essays of wit, rage, and reconciliation, Embalming Mom chronicles loss and renaissance in a life that reaches from Florida to Arizona across to England and home again. Burroway brilliantly weaves her way through the dangers of daily life--divorcing her first husband, raising two boys, establishing a new life, scattering her mother's ashes and sorting the meager possessions of her father. Each new danger and challenge highlight the tenacious will of the body and spirit to heal.